2008
DOI: 10.1002/jbm.a.31869
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of cell proliferation on tough gels by critical charge effect

Abstract: Tough triple network (TN) hydrogels that facilitate cell spreading and proliferation and, at the same time, preserve high mechanical strength are synthesized by the introduction of a proper component of negatively charged moiety, poly(2-acrylamido-2-methyl-propane sulfonic acid sodium salt) (PNaAMPS), on which cells proliferate, with neutral moiety, poly(N,N-dimethylacrylamide) (DMAAm), on which cells do not proliferate, as the third network component, to PNaAMPS/PDMAAm double network (DN) gels. For synthesizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 38 publications
(42 reference statements)
5
55
0
Order By: Relevance
“…This result is consistent with a previous study using endothelial cells on copolymer gels consist of dimethylacrylamide and sodium salt of 2-acrylamido-2-methyl-1-propanesulfonic acid (NaAMPS), P(NaAMPS-co-DMAAm) [14,15]. Electrostatic interaction between cells and negatively charged gels cannot explain the adhesion force between cells and the gels because the cell surface is also negatively charged.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is consistent with a previous study using endothelial cells on copolymer gels consist of dimethylacrylamide and sodium salt of 2-acrylamido-2-methyl-1-propanesulfonic acid (NaAMPS), P(NaAMPS-co-DMAAm) [14,15]. Electrostatic interaction between cells and negatively charged gels cannot explain the adhesion force between cells and the gels because the cell surface is also negatively charged.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that negatively charged polyelectroryte gels have potential in cell scaffolds [11], drug delivery system [12], and microfluidic system [13]. We have found that endothelial cells can spread, proliferate, and reach confluence on synthetic negative charged hydrogels without modification of adhesive proteins, and adhesion, attachment and proliferation of the cells depends strongly on the charge density [11,14,15]. This result shows that negative charged hydrogels have potential in using as blood vessel.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Three kinds of cells, i.e., BFAECs, human umbilical vein endothelial cells (HUVECs), and rabbit synovial tissue-derived fibroblast cells (RSTFCs), on poly(NaAMPS-co-DMAAm) hydrogels with various charge density were investigated [21].…”
Section: Ec Adhesion Spreading and Proliferation On Copolymer Hydrogelsmentioning
confidence: 99%